Sonographic Assessment of Retinal Detachment in diagnosed cases of Glaucoma - Summan Hameed, Syyeda Khadija, Zain Ul Hasan, Zobia Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To assess the retinal detachment in diagnosed cases of glaucoma in normal, diabetic, and hypertensive patients and to see the association of retinal detachment with diabetic and hypertensive patients. Study design: This study was cross-sectional analytical. Place & duration of study: This study was conducted at Mayo Hospital, Lahore from June 2020 to June 2022. Materials: The inclusion criteria was diagnosed glaucoma patients by an ophthalmologist. Exclusion criteria was Ophthalmologic surgery on the affected eye (prior 2 weeks). A sample size of 262 eyes was included in this research comprising 122 males (60.6%) and 79 females (39.3%). Data entry and analysis were done by using SPSS version-23. Results: Total number of 262 eyes (201 patients) were included in this research comprising 122 males (60.6%) and 79 females (39.4%). A total number of 140 patients with unilateral eye glaucoma were collected and 18 had a retinal detachment. And out of the 61 patients who had bilateral eye glaucoma 10 eyes had a retinal detachment. 46 patients had diabetes out of which 10 had a retinal detachment. 40 patients had hypertension out of which 6 had a retinal detachment. Practical implication: To prevent the vision loss of patients, prompt but accurate detection is essential to carry out appropriate treatment of retinal detachment and its complications. Due to its minimal effort of use, lack of radiation or contrast medium, and remarkable sensitivity and specificity, ultrasonography is the present first-line imaging evaluation for retinal detachment. Conclusion: The result of this investigation is that retinal detachment occurs in those patients suffering from glaucoma. Diabetes and hypertension affects eye health and aggravate abnormalities. Glaucoma-related vision loss could be reduced by identifying risk factors and drugs that enhance a patient's susceptibility to glaucoma and by recommending high-risk individuals for a comprehensive ophthalmologic checkup. Keywords: Glaucoma, Retinal Detachment, Diabetes Mellitus, Hypertension.